The Influence of Economic Literacy and Lifestyle on Impulse Buying Behavior of Students of SMA Negeri 2 Siak Hulu - Hanifah Fairuz; Sumarno Sumarno; Brilliant Asmit (Journal of Education Technology Information Social Sciences and Health, 2024)
This study aims to determine the effect of economic literacy and lifestyle on the impulse buying behavior of students at SMA Negeri 2 Siak Hulu. The population in this study were students of class XI IPS SMA Negeri 2 Siak Hulu with a total of 210 students. The sample of this research was 138 students with purposive sampling technique. The data collection method used a questionnaire containing tests and questionnaires which were distributed via the Google form and the data collected was then tabulated and analyzed using multiple linear regression. Hypothesis testing is done by partial significant test and simultaneous test. Based on the results of the study, it was found that economic literacy had a significant negative effect on the impulse buying behavior of students at SMA Negeri 2 Siak Hulu, lifestyle had a positive and significant effect on the impulse buying behavior of students at SMA Negeri 2 Siak Hulu, economic literacy and lifestyle had a positive and significant effect on impulse buying behavior of students of SMA Negeri 2 Siak Hulu.